Host preferences of root-associated fungi and their responses to decadal nitrogen and fungicide applications in an alpine pasture ecosystem - Hao Xi; Jing Zeng; Jiayao Han; Yali Zhang; Jianbin Pan; Qi Zhang; Huyuan Feng; Yongjun Liu (Journal of Integrative Agriculture, 2025)
Plant roots interact with diverse fungi that are essential for maintaining the productivity and sustainability of pasture ecosystems, but how these root-associated fungi (RAF) differ between forage species and how they respond to nutrient enrichment and fungicide application are not well understood. Here, we constructed an 11-year experiment involving fungicide application (with or without) nested within four levels of experimental nitrogen (N) addition treatments in an alpine pasture, and the RAF communities, root traits, tissue nutrients, and shoot biomass of two dominant forage species (Carex capillifolia and Elymus nutans) were analyzed. The RAF community composition showed striking differences between the plant species and was strongly affected by both N addition level and fungicide applications. Fungicide, but not N application, dramatically reduced the RAF richness of all functional guilds in both plant species, and fungicide also simplified the co-occurrence network of the RAF for C. capillifolia. The RAF community correlated strongly with root traits, whereas their relationships became weakened or even vanished at the level of the individual plant species. The importance of RAF to plant nutrients and productivity varied between plant species, with significant contributions in C. capillifolia but not in E. nutans. This is the first report elucidating the long-term effect of fungicides on RAF in alpine pastures, and our findings emphasize the host-specific responses of RAF community structure and function to anthropogenic disturbances.